The Cooperative Principle from Character Utterance in Paper Towns Movie (2015) - Samosir, Glorya; Ambalegin, Ambalegin (e-Journal of Linguistics; Vol 16 No 1 (2022): ejl-JanuaryDO - 10.24843/e-jl.2022.v16.i01.p15, 2021)
The movie's utterances were studied in a practical study based on Grice's cooperative principles theory (1989). The researchers took the date source from Paper Town movies that directed by Jake Schreier. In collecting of data, the researchers used observational data and non-participant technique (Sugiyono, 2010). The methodology that used by the researchers in analyze this research is descriptive-qualities (Creswell, J. W., & Creswell, 2017). The researchers put a lot of information about the theory such as, definition, explanation and also example. The outputs of this research are 15 utterances that identified as cooperative principle and the 4 four maxims of cooperative branches: In (1) Maxim Quality, the researchers found 2 data. Next, in the (2) Maxim Quantity the researchers found 5 data. After that, in the (3) Maxim Relation the researchers found 6 data. And in the last (4) Maxim Manner, the researchers found 2 data.